2005
DOI: 10.1074/mcp.m500076-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Sensitive Identification of Major Histocompatibility Complex Class I-associated Tumor Peptides by Nano-LC MALDI MS/MS

Abstract: Identification of major histocompatibility complex (MHC)-associated peptides recognized by T-lymphocytes is a crucial prerequisite for the detection and manipulation of specific immune responses in cancer, viral infections, and autoimmune diseases. Unfortunately immunogenic peptides are less abundant species present in highly complex mixtures of MHC-extracted material. Most peptide identification strategies use microcapillary LC coupled to nano-ESI MS/MS in a challenging on-line approach. Alternatively MALDI P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…In most cases, columns are 75-100 mm internal diameter columns and are directly coupled to mass spectrometers with an electrospray ionization (ESI) source in an on-line fashion (Salvi et al, 2008). Less frequently, LC separation can be used off-line to collect fractions that can be directly loaded onto MALDI targets (Hofmann et al, 2005). Liquid chromatography can also be used with strong cation exchange (SCX) media.…”
Section: Ms-based Strategies For Identificationmentioning
confidence: 99%
“…In most cases, columns are 75-100 mm internal diameter columns and are directly coupled to mass spectrometers with an electrospray ionization (ESI) source in an on-line fashion (Salvi et al, 2008). Less frequently, LC separation can be used off-line to collect fractions that can be directly loaded onto MALDI targets (Hofmann et al, 2005). Liquid chromatography can also be used with strong cation exchange (SCX) media.…”
Section: Ms-based Strategies For Identificationmentioning
confidence: 99%
“…Ankrd17 was serologically defined as breast cancer antigen NY-BR-16 and its peptide APRVPVQAL was identified as a major histocompatibility complex-associated tumor peptide (51,52) but its relevance to cancer is currently unknown. Recent study using kinase engineering strategy combined with chemical enrichment and mass spectrometry showed that Ankrd17 was a potential substrate of cyclin A/Cdk2 (53).…”
Section: Discussionmentioning
confidence: 99%
“…The method renders extraordinary molecular specificity to distinguish among the various forms of the circulating BNP, unlike the immunoassay and chemical tests commonly used. An off-line nano-HPLC (150 mm6100/75 lm id, C 18 ) -MALDI-TOF MS system was used for the identification of peptides encoded by cancer-related genes [49], with potential application in cancer immunotherapy. Very recently, an off-line micro-HPLC-MS system which consists of a PS-DVB monolithic column (50 mm6200 lm id) online coupled to a preconcentration trapping PS-…”
Section: Biomarker Peptidesmentioning
confidence: 99%